Voice recognition using machine learning and central database to enhance security system - Nur, Mir Md. Taosif; Dola, Sumaiya Sultana; Banik, Apurba Kishore; Akhter, Tanzeem; Hossain, Nafees (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.